INTERNET USE AMONG FACULTY MEMBERS OF COLLEGES OF EDUCATION IN SOUTHEASTERN NIGERIA - Onwuagboke, Bede Blaise Chukwunyere; Singh, Termit Kaur Ranjit; Fook, Fong Soon; Onwuagboke, Joy Ngozika (European Scientific Journal, ESJ, 2014)
This study is a descriptive survey which aims at finding out how faculty members in colleges of Education in south eastern Nigeria make use of the internet in their professional practices. A sample of 350 lecturers was proportionately randomly taken from faculty members in the colleges in the zone. A set of researcher made questionnaire tagged Internet Use Scale (IUS) was used to collect data from the respondents. Data collected was subjected to analysis using frequencies, percentages, t-tests and ANOVA. Findings revealed that Self-instruction, trial & error; organised training and workshops and Colleagues & friends assistance are the major source of internet training for faculty members. Similarly, Personal Laptop with modems; Personal mobile phones and Public cybercafé are the predominant mode of internet access available to faculty members. Significant differences exist between male and female faculty members with regards to internet use and frequency of use. There were also significant differences in internet uses and frequency of use between groups of faculty members according to teaching experience. The result has far reaching implication for provision of adequate training on Internet use in teaching and facilities to enhance effective teaching and learning in the colleges of education in the zone.